Estimating Willingness to Pay for Citarum River Water Quality Improvements using Benefit Transfer - Mabengba David Aja Kofi; Evi Gravitiani (Diponegoro Journal of Economics, 2025)
This study estimates households’ willingness to pay (WTP) for a 50% reduction in Citarum River pollution using a benefit transfer (BT) approach based on contingent valuation (CV) evidence from the Mekong River basin. The novelty of this study lies not in methodological innovation, but in the context-specific application of a function-based benefit transfer framework to one of Indonesia’s most polluted river systems, combined with explicit sensitivity and transfer-error analysis in a data-scarce setting. The paper contributes by demonstrating how BT can be responsibly applied as a screening and prioritization tool for environmental policy while clearly separating valuation results from speculative economic impact claims. Using a calibrated WTP function, the estimated mean WTP is IDR 45,000 (USD 3.10) per household per month, corresponding to an aggregated annual economic value of approximately IDR 5.4 trillion (USD 370 million) for 10 million households. Sensitivity analysis and a transfer error of 6.25% indicate acceptable reliability relative to international BT benchmarks. These findings provide policymakers with credible, transparent valuation evidence to inform river restoration planning and financing decisions in developing-country contexts where primary valuation data are limited.